3000 solved problems in organic chemistry - Meislich, Estelle K. (McGraw-Hill, 1994)
These books help readers review and master what they've learned by showing them how to solve thousands of relevant problems. Perfect for preparing for graduate or professional exams, these detailed reminders of problem-solving techniques show readers the best strategies for answering even the toughest questions, including the types that appear on typical tests